Rapid Production of Micro- and Nano-particles Using Supercritical Water - Fang, Zhen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book shows how to use supercritical water (SCW) to synthesize nano- and micro- oxides, inorganic salts and metal particles and its recent advancement. Also polymer/biomass particles can be produced by using the method of precipitation of solutes from SCW. The particles can be used as catalysts for biomass conversions, materials in ceramics & electronic devices and composite materials. Particles are easily produced continuously in a flow reactor in short reaction times or synthesized in a batch reactor in long reaction times. Besides the synthesis process, the book also present studies of the properties of these materials. The size, size distribution, crystal growth & structure, and morphology of particles produced by supercritical water can be controlled by the feed concentrations, pH, pressures, temperatures, heating & cooling rates, organic modifications, reducing or oxidizing atmospheres, flow rates and reaction times.
Supercritical Water Process -- Metal Oxides Synthesis -- Nano-Structured Coatings -- Other Materials Synthesis -- Fine Organics Particles by Precipitation of Solute -- Conclusions and Future Prospects.
Keywords: Catalysis; Engineering; Nanotechnology; Surfaces (Physics).; Materials Science; Nanotechnology; Nanotechnology and Microengineering; Characterization and Evaluation of Materials; Catalysis